Should Echocardiographic Evaluation Be Performed Routinely in the First 72 Hours in Extremely Low Birth Weight Babies? - Colak, Ruya; Alkan Ozdemir, Senem; Yangin Ergon, Ezgi; Kulali, Ferit; Kalkanli, Oguz Han; Gokmen Yildirim, Tulin; Yilmazer, Murat Muhtar; Zihni, Cuneyt; Calkavur, Sebnem (Gynecology Obstetrics & Reproductive Medicine, 2021)
Objective: Hemodynamically significant patent ductus arteriosus(hsPDA) is resulting in severe mortality and morbidity in infants with extremely low birth weight(ELBW). In our study, we aimed to evaluate the necessity of performing routine echocardiography(ECHO) in the first 72hours in ELBW infants. Study Design:This study was planned retrospectively and observationally.Between June2016 and December2018,36 patients diagnosed with hemodynamically significant PDA(hsPDA) who were hospitalized in the neonatal intensive care unit(NICU),with ≤28Gw or ≤1000g were included in this study.These babies were routinely performed ECHO for PDA between 24-72hours,although they were asymptomatic in the period from June2016 to December2017(n:23).Between January2018 and December2018, patients without PDA symptoms were expected to complete 72hours for routine PDA screening (n:13).The patients were divided into 2 groups as early ECHO group(EEG)(n=23) and late ECHO group (LEG)(n=13).In the presence of at least one of the clinical signs of systemic hypoperfusion and/or pulmonary hyperperfusion, symptomatic PDA was accepted and closure treatment was applied with ibuprofen(n: 23) or paracetamol(n: 5).While the two groups were compared in terms of demographic features,ECHO findings,and the state of taking closure therapy,patients receiving closure therapy were compared in terms of mortality and premature morbidity. Results:The average birth weight of 36 patients was 855.9(± 241.5)g, and the average week of birth was 26.4(± 2.1)Gw.It was observed that the two groups were similar in terms of demographic characteristics.Although the findings of ECHO and treatment rates were similar between the two groups,it was observed that the EEG had earlier closure treatment(p = 0.03). In patients receiving closure treatment, performing early(n:17)and late(n:11) echocardiography showed no statistical difference in the long-term results. Conclusion:Performing early ECHO without symptoms in infants with ELBW may provoke the clinician to give PDA closure treatment earlier. In infants with ELBW,unnecessary closure treatment can be prevented by closely monitoring the symptoms of PDA and performing ECHO when necessary.